Aspects of the granulomatous reaction in the liver of mice infected and reinfected with two different geographical strains of Schistosoma mansoni - Pedro Raso; Paulo Marcos Z. Coelho; Nivaldo H. Toppa; Rômulo T. Mello (Revista da Sociedade Brasileira de Medicina Tropical, 1994)
In this study, which was undertaken in relation to the histopathologic behavior of two different strains (LE-Belo Horizonte, MG and SJ - São José dos Campos, SP) in infections and reinfections (homologous or heterologous) with Schistosoma mansoni, the authors confirmed a more accentuated pathogenicity of the SJ strain. All the reinfections showed the presence of typical granulomas of the acute phase, when performed either with the same strain (homologous) or with a different strain (heterologous) of the parasite of the primo infection. The possible mechanisms responsible for reactivation of the immunopathologic response in reinfections are discussed. No presente estudo, verificou-se o comportamento histopatológico das infecções e reinfecções, homólogas ou heterólogas, das cepas LE (Belo Horizonte, MG) e SJ (São José dos Campos, SP) de Schistosoma mansoni. Confirmou-se uma maior patogenicidade da cepa SJ de S. mansoni. As reinfecções, independentemente de terem sido feitas com a mesma cepa (homóloga) ou cepa diferente da primo infecção (heteróloga) do parasito, mostraram a presença de granulomas típicos da fase aguda. São discutidos os possíveis mecanismos responsáveis pela reagudização da resposta imunopatológica nas reinfecções.